Sliding on DNA: From Peptides to Small Molecules. Issue 48 (4th November 2016) - Xiong, Kan; Erwin, Graham S.; Ansari, Aseem Z.; Blainey, Paul C.
Abstract: Many DNA binding proteins utilize one‐dimensional (1D) diffusion along DNA to accelerate their DNA target recognition. Although 1D diffusion of proteins along DNA has been studied for decades, a quantitative understanding is only beginning to emerge and few chemical tools are available to apply 1D diffusion as a design principle. Recently, we discovered that peptides can bind and slide along DNA—even transporting cargo along DNA. Such molecules are known as molecular sleds. Here, to advance our understanding of structure–function relationships governing sequence nonspecific DNA interaction of natural molecular sleds and to explore the potential for controlling sliding activity, we test the DNA binding and sliding activities of chemically modified peptides and analogs, and show that synthetic small molecules can slide on DNA. We found new ways to control molecular sled activity, novel small‐molecule synthetic sleds, and molecular sled activity in N‐methylpyrrole/N‐methylimidazole polyamides that helps explain how these molecules locate rare target sites. Abstract : Synthetic small molecules with a wide range of chemical functionality can slide on DNA, and specific modifications can be used to tune crucial properties like DNA affinity and sliding speed. The picture shows a polyamide bound to DNA and its trajectory when sliding on DNA.